If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -22p + -6(2 + -5p) = 6(p + -2) + -16 -22p + (2 * -6 + -5p * -6) = 6(p + -2) + -16 -22p + (-12 + 30p) = 6(p + -2) + -16 Reorder the terms: -12 + -22p + 30p = 6(p + -2) + -16 Combine like terms: -22p + 30p = 8p -12 + 8p = 6(p + -2) + -16 Reorder the terms: -12 + 8p = 6(-2 + p) + -16 -12 + 8p = (-2 * 6 + p * 6) + -16 -12 + 8p = (-12 + 6p) + -16 Reorder the terms: -12 + 8p = -12 + -16 + 6p Combine like terms: -12 + -16 = -28 -12 + 8p = -28 + 6p Solving -12 + 8p = -28 + 6p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-6p' to each side of the equation. -12 + 8p + -6p = -28 + 6p + -6p Combine like terms: 8p + -6p = 2p -12 + 2p = -28 + 6p + -6p Combine like terms: 6p + -6p = 0 -12 + 2p = -28 + 0 -12 + 2p = -28 Add '12' to each side of the equation. -12 + 12 + 2p = -28 + 12 Combine like terms: -12 + 12 = 0 0 + 2p = -28 + 12 2p = -28 + 12 Combine like terms: -28 + 12 = -16 2p = -16 Divide each side by '2'. p = -8 Simplifying p = -8
| 10+3=6x-9 | | 2a-6a=0 | | 4h+24h=20 | | 25/3/5=m | | -3x+4y=20 | | (2a-3)+(3a-1)= | | 20-5y/2=x | | (3x+5y)dx+(4x+6y)dy=0 | | 1/2y^2-5/2y-12 | | 5(5x-3)+11=-3 | | 15w^2-1w-2=0 | | 0.5(x+100)+1.3x=131 | | (-7/3u-9)-4=(-8/u-3) | | x^2/10+x+2/3=0 | | 0.6x+8.1=7.2 | | 5x-3-4x-10=27 | | 2+2x/7+5-x/5+48/35 | | 3x^9-15x^8=9x^7 | | X^2-12X-676=0 | | 5(5x-3)+11=3 | | -2[5(x-2)-10]=80 | | 0.25x^2-1/2x=1 | | 2x+3-5=-3 | | 18-(3x+5)=8 | | 10(a-1)-2(a+2)+3=13 | | 9(4-y)+2=-2(y-4)-3 | | 8x-1+4=6 | | .16(y-1)+.06y=.18y-.3 | | 7-6x/4 | | 7-4/x | | 5x-y=100 | | .75x+.05(20-x)=.10(-46) |